The Effect of E-Service Quality on Customer Satisfaction of the Welma Application at PT Bank Central Asia, TBK - Hendy Setiady; Marlina Widiyanti; Ahmad Maulana; Aslamia Rosa (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to examine the influence of electronic service quality (e-service quality) on customer satisfaction with the Welma application at PT Bank Central Asia, Tbk. The method used is a survey using a questionnaire distributed to customers of the Welma application. The data analysis technique used is multiple linear regression analysis. The sample of this study is 400 respondents of Welma application customers who were selected by convenience sampling. The results of the study show that there is a positive and significant influence of electronic service quality on customer satisfaction with the Welma application. The implication of the results of this study is the importance of PT Bank Central Asia, Tbk to continue to improve the quality of electronic services to increase customer satisfaction of the Welma application so that it can retain and attract more customers.